2020
DOI: 10.1038/s41433-020-1054-2
|View full text |Cite
|
Sign up to set email alerts
|

Microperimetry and mfERG as functional measurements in diabetic macular oedema undergoing intravitreal ranibizumab treatment

Abstract: Purpose To evaluate Microperimetry (MP) and multifocal electroretinogram (mfERG) as whole-macula functional markers of treatment response in naive diabetic macular oedema (DMO) patients undergoing ranibizumab treatment. Methods An exploratory sub-analysis of a prospective study (NCT01947881-CHARTRES). Patients received three monthly ranibizumab injections (loading dose) followed by pro re nata (PRN) regimen during 1 year. At baseline, during and after treatment (Months 0, 3, 6 and 12), subjects were tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Santos et al compared the results between mfERG and FP in diabetic macular edema and concluded that both were able to demonstrate a functional improvement after intravitreal treatment with ranibizumab. 47 In general, fundus perimetry seems to perform as well as electrophysiology examination in detecting retinal alterations in different pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al compared the results between mfERG and FP in diabetic macular edema and concluded that both were able to demonstrate a functional improvement after intravitreal treatment with ranibizumab. 47 In general, fundus perimetry seems to perform as well as electrophysiology examination in detecting retinal alterations in different pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…5). 48,65,66 In the ProgStar6 and Tanna et al64 studies, the baseline VTOT in adults was 0.91 and 0.52 dB-sr with an annual decline of 0.077 to 0.06 dB-sr, respectively. In children, these values were a baseline VTOT of 0.87 dB and an annual decline of 0.21 dB-sr.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, Santos and colleagues reported that better retinal sensitivities before treatment were associated with better BCVA outcomes after therapy. This suggested that the baseline MP findings may have prognostic value for DME treatments 89. Yohannan et al90 further demonstrated that disruption of the ellipsoid zone is correlated with a significant decrease in the point sensitivity in eyes with DME.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations